Pengaruh Teknik Silase Pakan Komplit Tersuplementasi Ampas Tahu Berprotein Kasar Berlebih pada Domba Secara InVivo - Tekad Urip Pambudi Sujarnoko; dwi budiono; Dudi Firmansyah; Tenti Rahmawati (Jurnal Ilmiah Fillia Cendekia, 2023)
Tofu dregs are feed ingredients with high nutritional content and easy to rot. Therefore a silage storage technique is needed to preserve and reduce environmental pollution. The process of preserving high-protein feed by silage has a weakness in the process of lowering the pH. This happens because the ammonia from the deamination process is alkaline . The silage processing can converting some nutrients into organic acids which can improve livestock health and production. The Complete feed silage which was supplemented with tofu dregs was carried out on thin-tailed local rams aged 8-10 months and body weight 16-18 kg. The rams were grouped to 4 groups. The first gorup was P0 = complete feed which was suplemented with tofu dregs without silage processing compared to P1 = P0 + silage processing which was fermented for at least 14 days. The data then analyzed using t-independent method in a randomized block design on the basis of body weight. The results of the study showed that the average dry matter consumption of livestock was not significantly different P>0.1, the increase in monthly weight was higher in group P1 with a P value <0.05, the silage process increased the efficiency of p<0.05. Both treatment had no effect on cholesterol, blood urea nitrogen (BUN), glucose, red blood grains and white blood grains. So it can be concluded that feeding by silage is better than fresh . Keywords: Silage, rams, tofu dregs